PERANCANGAN CETAK BIRU TEKNOLOGI INFORMASI UNIVERSITAS BINA DARMA - Andryani, Ria (JURNAL ILMIAH MATRIK, 2013)
The use of information technology is growing due to the condition of the business environment is changing rapidly, so the ability to get information immediately have a competitive advantage. To achieve competitive advantage, company or organization needs to build IT (Information Technology) Master Plan that governs all investment policies and implementation of information technology. Bina Darma University is one of the colleges that run the education system by utilizing information technology, in accordance with the vision and mission of a university-based international berstrandar technology in 2025. To achieve the mission and vision needed IT Masterplan that can serve as guidelines in the investment and implementation of IT in Universitas Bina Darma. IT Development Masterplan is to use SWOT analysis to determine the strength of the IT map in Universitas Bina Darma. Research results indicate is necessary to develop the Master Plan refers to the information technology business strategy and strategic management of IS / IT. Keywords: Information Technology, Masterplan, SWOT Analisys, TOWS.